Solid phase microextraction-gas chromatography for the analysis of explosives in post blast water samples - Ahmad, Umi Kalthom; Kiu, Kee Heng (Penerbit UTM Press, 2007)

(untitled)
In this study, a solid-phase microextraction (SPME) technique followed by gas chromatography (GC) was used to determine explosive residues. Several parameters including adsorption time, desorption time and temperature, SPME fiber types, stirring effect and salting out effect were optimized to obtain reproducible data with good accuracy. Addition of 10% w/v of NaCl in the aqueous medium and the use of a Carboxen/Polydimethylsiloxane (CAR/PDMS) fiber coating led to optimal extraction efficiencies. The optimized SPME/GC-ECD method was applied to the trace analysis of explosive residues in water samples. 2,6-dinitrotoluene (2,6-DNT), trinitrotoluene (TNT) and pentaerythritol tetranitrate (PETN) were successfully detected from water samples. Direct Immersion SPME/GC-ECD was found to be an attractive technique for qualitative and quantitative analysis of explosives in post blast water samples.